Faktor-Faktor yang Mempengaruhi Praktik Perataan Laba pada Perusahaan Asing dan Non Asing di Indonesia - Muhammad Yusuf; Soraya Soraya (Jurnal Akuntansi dan Auditing Indonesia, 2004)
This research is designed to examine factors that can be identified with the incidence of income smoothing practice among listed companies at Jakarta Stock Exchange. Those factors were size, profitability, operating leverage and status of the companies. Univariate tests (Mann-Whitney, Chi-Square and T-Test) and multivariate tests (logistic regression) were used to identify the factors affecting the income smoothing practice. The result of indeks’ eckel calculation showed that income smoothing is practiced by listed companies on the JSX. The test result of univariate tests also showed that operating leverage of the companies is the variable having a significant correlation with the income smoothing practice. In addition, the operating leverage of the companies has a significant influ¬ence on the income smoothing practice if it is not combined with another variable, such as: size, prof¬itability and status of the companies.